Secretory carcinoma of the breast with multiple distant metastases in the brain and unfavorable prognosis: a case report and literature review - Hongping Tang; Lihua Zhong; Hongbing Jiang; Yan Zhang; Guannan Liang; Guoyan Chen; Gui'e Xie (BMC, 2021)
Abstract Background Secretory carcinoma of the breast is one of the rarest entities, accounting for less than 0.15 % of all infiltrating breast carcinomas. It has characteristic histopathological and molecular features and, in general, a more favorable prognosis. In this case report, we describe a local, advanced secretory carcinoma of the breast with aggressive course and an unfavorable outcome. Case presentation A hard, painless, and palpably bossed mass approximately 12.0 cm in diameter occupied most of the left breast of a 39-year-old woman with fixation to the overlying skin. Breast ultrasonography and magnetic resonance imaging (MRI) scans gave the same grading as BI-RADS IV. A needle biopsy was performed, and the pathological diagnosis was secretory carcinoma. Neoadjuvant chemotherapy (NAC) was then performed, after which ultrasonography and MRI scans revealed chemo-resistance of the tumor to NAC. Left breast mastectomy and axillary lymphadenectomy were subsequently performed. Tumor cells were triple-negative and positive for S-100 and periodic acid-Schiff (PAS) staining. Fluorescence in-situ hybridization (FISH) analysis indicated a fusion arrangement of the ETV6-NTRK3 gene. The patient developed multiple distant metastases in the brain and died of these metastases 19 months after initial diagnosis. Conclusions Secretory carcinomas of the breast have been described as a low-grade histologic subtype with a favorable prognosis. This case showed chemo-resistance to neoadjuvant chemotherapy, multiple distant metastases, and a final unfavorable outcome. Further research is needed to better understand the behavior and treatment of this rare tumor.